Impact of COVID-19 lockdown on meat or equivalent consumption behavior among Sri Lankan adults: a cross-sectional study - Gamage, Manoja; Sooriyaarachchi, Piumika; Francis, Tormalli; Jayawardena, Ranil (Journal of Ideas in Health, 2022)
Background: The COVID-19 lockdown severely affected dietary behaviors, particularly meat or equivalent consumption. This study aimed to understand the impact of COVID-19 confinement on meat or equivalent consumption pattern among Sri Lankans. Methods: A cross-sectional study was conducted from 27th May to 2nd June 2021 as a national-level online survey in Sri Lanka using a self-administered questionnaire developed as Google forms. The questionnaire consisted of questions related to socio-demographics and dietary behaviors. Descriptive, univariate, and multinomial logistic regression was performed. The statistical significance is considered at less than 0.05. Results: A total of 3600 respondents were included, with the majority being women (60.1%). A higher proportion of the participants increased their consumption of eggs (53.7%), dhal (47.0%), and dry fish and sprats (36.3%). A big trend was observed in cutting down the fish (41.1%) and other seafood (52.0%) consumption. Nearly half of the respondents did not change their consumption of meat other than chicken (54.5%), pulses (52.6%), soya meat (52.1%), dry fish and sprats (48.9%), canned fish (47.6%), sausages and meatballs (45.1%), and chicken (43.7%). The males (odds ratio (OR) 0.852; 95% CI: 0.738 to 0.984, P = 0.029) and Tamil (OR = 1.605, 95% CI: 1.150 to 2.239, P = 0.005) showed a significant likelihood to increase egg consumption. Respondents with a lower income <25,000 LKR (OR 2.220; 95% CI 1.672-2.947, P = 0.000) were more than twice likely to report increased dhal consumption. The same income group (< 25,000 LKR) (OR = 2.752; 95% CI: 2.024-3.741, P = 0.000) reported more than twice reduction in fish consumption. Respondents in municipal area (OR = 1.523; 95% CI: 1.186 to 3.292, P = 0.009) showed a significantly higher likelihood to reduction in other seafood consumption. Conclusion: An overall change in meat or equivalent consumption behavior among Sri Lankan adults was evidenced. Furthermore, nutrition recommendations should be revised to avoid future long-term consequences. Fish and other seafood intake declined, while consumption of eggs, dhal, dry fish, and sprats increased.